Ensuring the correctness of adaptive business processes: a systematic literature review. (10th April 2020) - Fakhfakh, Fairouz; Kacem, Hatem Hadj; Kacem, Ahmed Hadj
Adaptability in process management systems is gaining an increasing attention to satisfy the variable enterprise requirements. This concept has been recognised by the process community for a long time and various approaches in this area have been developed so far. In this context, one of the most difficult challenges is to ensure that change operations are applied correctly and do not cause any inconsistencies. This paper presents a survey that examines the existing studies ensuring the correctness of process changes. Our survey follows the guidelines of Systematic Literature Review (SLR). It provides a comparison of the existing approaches based on some criteria such as verified properties, modelling languages and verification tools. Finally, we highlight some recommendations and possible future researches which need further investigations. So, throughout this present paper, we provide information for researchers and developers to understand the contributions and challenges of the current studies to pave the way for improving their solution.